In Vivo Evaluation of Anti-inflammatory Activity of TopicalPreparations from Fenugreek(Trigonella foenum-graecumL.)Seeds in a Cream Base: Topical anti-inflammatory preparations of fenugreekh - Fariba Sharififar; Payam Khazaeli; Narguess Alli (Iranian Journal of Pharmaceutical Sciences, 2009)
Fenugreek (Trigonella foeum-graecumL.) has been used in Iranian traditional medicine for treatment of different kinds of inflammation disorders. In the present study, anti- inflammatory activity of the methanolic extract of the plant (at doses of 100, 200 and 400 mg/kg) were studied using carrageenan-induced edema method and compared with the effects of dexamethasone and ibuprofen. Various concentrations of the plant extract (2-5%) were also prepared as a cream and their anti-inflammatory effects were evaluated and compared with 1% hydrocortisone ointment as the reference drug. The results showed that the inhibition of edema by the plant extract at doses of 100 and 200 mg/kg were significantly different from the control group. This activity of the plant at doses of 100 and 200 was not significantly different from those of ibuprofen and dexamethasone. Among the prepared formulations of the plant, 3 and 5% creams of the fenugreek showed themost inhibition of edema which were not significant from hydrocortisone ointment.The results of the present study, therefore, support the traditional uses of this plant for inflammations. However, more research is needed for its use in clinical studies.